Conformational Studies of Oligosaccharides - Yu, Yang; Delbianco, Martina (Chemistry : a European journal, 2020)
The conformation of a molecule strongly affects its function, as demonstrated for peptides and nucleic acids. This correlation is much less established for carbohydrates, the most abundant organic materials in nature. Recent advances in synthetic and analytical techniques have enabled the study of carbohydrates at the molecular level. Recurrent structural features were identified as responsible for particular biological activities or material properties. In this Minireview, recent achievements in the structural characterization of carbohydrates, enabled by systematic studies of chemically defined oligosaccharides, are discussed. These findings can guide the development of more potent glycomimetics. Synthetic carbohydrate materials by design can be envisioned. Chemical synthesis and novel analytical techniques have enabled conformational studies of oligosaccharides. Recurrent structural features have been identified. Tuning these structures will allow for the production of more potent glycomimetics and materials by design.